Profiling the context of natural history teacher candidate for the elementary school degree through web-based inquiry - Pramita Sylvia Dewi; Diana Rochintaniawati; Parsaoran Siahaan (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2020)
Web-Based Inquiry is an important investigative activity that should be implemented in the classroom. Such investigative activity, or investigation in general, serves as the basis for a researcher to develop his or her study. In relation to this initiative, the ICT-based learning capacity becomes a significant part since this capacity serves as the basis for the utilization of the Web-Based Inquiry, which has been marked by the capacity of operating the overall investigation information from the ICT-based learning. Departing from this elaboration, the objective of the study is to describe the capacity of ICT information and the delivery of the preliminary information for the needs of the Web-Based Inquiry. During the conduct of the study, the purposive sampling technique was implemented in order to define the number of the sample. As a result, 66 students from Batch 2019 of Lampung University were selected as the subjects for the study. Then, the data gathering instrument that had been implemented was the investigation (ICT-Based Learning) questionnaire. The data that had been gathered then were descriptively analysed. The results of the study show that the biggest data portion has been found in the use of the Internet-accessing tool although the score of this biggest portion falls into the “Low” category (under 25%). Thus, it might be implied that the Natural History teacher candidates have relatively not internalized the awareness and the best innovation in combining the lesson and the use of ICT through the ways that are more understandable for the students.